Kualitas Kepemimpinan Pemuda dalam Gereja menurut 1 Timotius 4:12 - Landong Siringoringo; Yeghar Galed Laransedu; Razat Simarmata (Lembaga Pengembangan Kinerja Dosen, 2025)
Leadership is a very important aspect in various organizations, including church organizations. There are many leadership characteristics in the Bible that can serve as models for leadership in the church. This article is a literature review using a qualitative approach to the text of 1 Timothy 4:12, focusing on the leadership of a young person. Its purpose is to encourage students to understand and apply the leadership model mentioned in 1 Timothy 4:12. The method used is descriptive analysis of the text of 1 Timothy 4:12, in order to provide a clear picture and understanding of the principles of young leadership. In addition, the descriptive method is also used to assess students’ understanding of leadership principles based on the text, as well as the level of their application in life and ministry. In conclusion, students understand the leadership principles in 1 Timothy 4:12, especially the importance of being an example, where the quality of a young person’s character is not merely theoretical, but students are able to live it out.